Description of Oromurcia magadanensis sp. nov. (Acari, Oribatida, Ceratozetidae) from Russia, with remarks on biogeography of the genus Oromurcia Thor, 1930 - ERMILOV, SERGEY G.; MAKAROVA, OLGA L.; BEHAN-PELLETIER, VALERIE M. (Zootaxa, 2022)
Species of the genus Oromurcia Thor, 1930 (Oribatida, Ceratozetidae) mainly have an arctic or alpine distribution in the Western Palaearctic region and Greenland. We describe a new species of Oromurcia from Northeast Asia (Magadan Region, Russia) based on adult and juvenile instars. Numerous populations of Oromurcia magadanensis sp. nov. were found under arctic-alpine plants in a narrow stream gully with large snow accumulation on the Ola Plateau (1023 m a.s.l.). Adults of Oromurcia magadanensis sp. nov. differ from those of Oromurcia bicuspidata and O. sudetica by their smaller size, the presence of clavate, distally broadly rounded bothridial seta, tutorium with several teeth distally, and the absence of striations on the lamella. Juvenile instars of the new species differ from those of O. bicuspidata and O. sudetica by the presence of medium-sized gastronotic setae in the larva, and long lateral and posterior gastronotic setae in nymphs. We compare adult and juveniles of Oromurcia magadanensis sp. nov. with those of other members of the ceratozetid subfamily Trichoribatinae Shaldybina, 1966 from arctic or alpine regions, for which ontogeny is known, and provide revised diagnoses for adult and juvenile members of Trichoribatinae. All Oromurcia species are associated with cold wet places (periglacial habitats, bogs and fens, alpine meadows, snowbeds, and, less frequently, montane coniferous forests) in Eastern and Western Palaearctic, but they are absent from High Arctic and Siberian regions that are ultra-cold in winter. This spatial disjunction argues for a former Trans-Palaearctic range that was possibly subdivided by reсurrent cryo-arid Pleistocene episodes.